E DÉUS PERDÓ A PAPA MARTÍ ("QUE DIOS PERDONE AL PAPA MARTÍN"): ALGUNOS ASPECTOS DE LA VISION DEL PAPADO EN LA CRONICA DE RAMON MUNTANE (Res Publica. Revista de Historia de las Ideas Políticas, 2023)
The article takes a look at Ramon Muntaner’s Crónica, other medieval chronicles y the diplomatic relations of the time in order to test their internal coherence. Indeed, all of these sources coincide in offering us an idea which characterises the policies of the House of Aragon in the Mediterranean as hostile to the axis of power which dominated the High Middle Ages, the royalty in Paris and the Holy See of Rome. Such hostility, however, contrasted with the religious function which the House of Aragon had itself. Thus, it was not hostility towards the Papacy, but rather towards the Papal dedication to the defence of French interests, above all in Sicily and Naples.